Importance of implementing the sustainable development goals for students in the MERCOSUR and the experience of South Korea - Marino, Soraia (Handbook of Research on Current Advances and Challenges of Borderlands, Migration, and Geopolitics, 2024)
The sustainable development goals are a fundamental framework for universities that want to extend their impact. Not only to education but also transversally into all of the agenda 2030 advocating the well-being of the people. The students are capable of creating sustainable and innovative solutions while building a close bond with the local and international community. MERCOSUR universities, in this complex world, can be benefited in two-ways. First, as part of a solution to social problems with a sustainable development approach and, lately, as part of raising the awareness to the competition of the agenda 2030. This chapter aims to contribute to research and practice fostering discussions and sharing knowledge about the importance that the sustainable development goals have in the students of the MERCOSUR.
Keywords: sustainable development goals; students; MERCOSUR; South Korea; Scopus(2)